Peer Support and Outcome Expectations in STEM: Development and Validation of an Instrument - Deneb Elí Magaña Medina; Verónica Hernández-Mena; Norma Aguilar Morales; Pedro Antonio Sánchez Escobedo (Universidad Autónoma de Baja California, 2023)
Identifying the factors that influence young Mexicans' choice of career is essential to generate strategies able to attract new students to science, technology, engineering, and mathematics (STEM). The objective of this study was to develop and verify the psychometric properties (realibility and construct validity) of the scales "Student peer support" (APE-STEM) and "Outcome expectations" (EXREC-STEM) in high school students' choice of STEM college degrees by generating a structural equation model. Likert scales were administered to 167 students from rural and urban schools in southeastern Mexico. The results of the exploratory and confirmatory factor analyses show adequate fit and an internal consistency of α= .82 and .84, confirming the empirical soundness of the model and leading to the conclusion that these scales are highly reliable for use in this context.